2014
DOI: 10.1097/mao.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Hearing Preservation in Electric-Acoustic Stimulation Patients

Abstract: Long-term HP in EAS users after HP surgery is feasible, although a small continuous decline of HP rate of 3% per year was observed (measured from first fitting up to 6 years postoperative). Nevertheless, a continuous improvement was found in the speech perception results of the EAS users across 10 years. Moreover, the positive subjective benefit, assessed 3 months postoperative, remained stable up to 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
2
16
1
2
Order By: Relevance
“…Mertens et al reported the HP rates of 11 ears implanted with three different electrodes, with implant experience ranging from 3 to 10 years. They found that 27% patients had complete preservation, 45% had partial preservation, 18% had minimal preservation, and 9% completely lost their hearing (27). Santa Maria et al (26) also used the Skarzynski et al formula in evaluating 14 patients implanted with the Flex24 electrode.…”
Section: Discussionmentioning
confidence: 95%
“…Mertens et al reported the HP rates of 11 ears implanted with three different electrodes, with implant experience ranging from 3 to 10 years. They found that 27% patients had complete preservation, 45% had partial preservation, 18% had minimal preservation, and 9% completely lost their hearing (27). Santa Maria et al (26) also used the Skarzynski et al formula in evaluating 14 patients implanted with the Flex24 electrode.…”
Section: Discussionmentioning
confidence: 95%
“…This may relate to the pathology of the individual reason for hearing loss, thus, the patient did not have a stable hearing loss prior to surgery, but is in most cases likely to depend on an intracochlear process leading to hearing deterioration. The nine subjects Mertens and colleagues (Mertens et al, 2014) followed for up to eleven years a gradual loss was seen for most of them. Erixon and co-workers (Erixon et al, 2015) followed 19 patients for up to three years, displaying a gradual low frequency loss and recently Helbig et al reported on a large number of patients (n=96) that were followed up to eleven years (Helbig et al, 2016).…”
Section: Hearing Preservation During Cochlear Implantationmentioning
confidence: 96%
“…In recent years, clinical studies evaluated long-term outcomes of cochlear implantation in patients with residual hearing. Mertens et al (Mertens et al, 2014) described a group of 9 patients (11 ears), followed for 10 years, showing complete low-frequency hearing preservation in 27%, partial preservation in 45%, minimal in 18% and loss of residual hearing in one subject. This study used the HEARRING group Hearing Preservation Classification System (0% = loss of hearing; >0%-25% = minimal HP; >25%-75% = partial HP; >75% = complete HP) to evaluate hearing preservation rates and compare results of different strategies of intervention.…”
Section: Surgery and Residual Hearingmentioning
confidence: 99%
“…HP results reported for other manufacturers' electrodes report slightly lower percentages of complete and partial preservation than found here. Mertens et al 19 found that 27% subjects had complete HP, 45% had partial HP, and Santa Maria et al 20 found that 22.2% had complete HP and 66.7% partial HP. However, although larger than our sample, group sizes were still less than 20 subjects.…”
Section: Discussionmentioning
confidence: 99%